EFEKTIVITAS REZIM PROLIFERATION SECURITY INITIATIVE (PSI) DALAM MENANGKAL PROGRAM SENJATA NUKLIR KOREA UTARA - Nurazizah, Siti Nurazizah; Olivia, Yessi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This thesis discusses the effectiveness of the Proliferation Security Initiative (PSI) regime in countering North Korea's nuclear weapons program. Specifically, this thesis discusses the efforts of the international community and the United States to work together to establish a PSI regime as a response to the threat of nuclear weapons programs and spread by rogue states, one of which is North Korea. PSI is a global effort to stop the spread of weapons of mass destruction (WMD), delivery systems and related materials to and from state actors and non-state actors of proliferation concern. Using descriptive qualitative research methods, the author analyzes PSI's efforts to counter North Korea's nuclear weapons program using the theory of international regime effectiveness proposed by Underdal to measure the effectiveness of the PSI regime in countering North Korea's nuclear weapons program. The effectiveness of a regime can be tested based on the complexity of the problem faced. Analysis of the effectiveness of the PSI regime in countering North Korea's nuclear weapons program can be described as quite complex and limited. Complexities within the PSI regime itself, such as gaps in intelligence and understanding of North Korea's activities and intentions, could become obstacles in designing and implementing effective strategies to suppress its nuclear program. Limited access to accurate and complete information about North Korea's nuclear installations also makes intervention efforts difficult. The ineffectiveness of PSI is also based on limited international cooperation, lack of initiative from all member countries or other countries to fully cooperate in implementing this regime. lack of cooperation reduces PSI's effectiveness in preventing North Korean nuclear proliferation Keywords: PSI, North Korea, Weapon of Mass Destruction, International Regime